2017
DOI: 10.7554/elife.22599
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor neddylation is regulated by a desmosomal-COP9 (Constitutive Photomorphogenesis 9) signalosome complex

Abstract: Cell junctions are scaffolds that integrate mechanical and chemical signaling. We previously showed that a desmosomal cadherin promotes keratinocyte differentiation in an adhesion-independent manner by dampening Epidermal Growth Factor Receptor (EGFR) activity. Here we identify a potential mechanism by which desmosomes assist the de-neddylating COP9 signalosome (CSN) in attenuating EGFR through an association between the Cops3 subunit of the CSN and desmosomal components, Desmoglein1 (Dsg1) and Desmoplakin (Dp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…This dampened EGFR signaling and consequently cell division, and allowed differentiation to proceed. These data support a model where DSG1-dependent scaffolding of the COP9 signalosome facilitates epidermal differentiation by controlling EGFR dynamics ( Najor et al, 2017 ).…”
Section: Desmosomal Proteins As Effectors: Control Of Proliferationsupporting
confidence: 84%
“…This dampened EGFR signaling and consequently cell division, and allowed differentiation to proceed. These data support a model where DSG1-dependent scaffolding of the COP9 signalosome facilitates epidermal differentiation by controlling EGFR dynamics ( Najor et al, 2017 ).…”
Section: Desmosomal Proteins As Effectors: Control Of Proliferationsupporting
confidence: 84%
“…Several recent reports have highlighted the potential for non-canonical NEDDylation to result in a target protein’s destabilization and destruction. The first substrate identified that could be destabilized and destroyed following NEDD8 conjugation was the epithelial growth factor receptor (EGFR) [ 40 , 41 ]. Other proteins soon joined the list of substrates that could be destabilized and degraded following NEDDylation including HDAC, JunB, SMF2, c-Src, SRSF3, Ajuba, and E2F-1 [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…EGFR is stabilized at the plasma membrane in part by the process of neddylation, the addition of Nedd8 moieties to the C‐terminus. De‐neddylation is mediated by a large protein complex, the COPS9 signalosome, and results in the ubiquitination of EGFR and turnover of the receptor (Najor et al., 2017). ( A ) PLA using an antibody pair recognizing EGFR mouse and the Nedd8 moiety rabbit demonstrates the level of post‐translational modification of EGFR in the epithelial cells, visualized by PLA reaction “spots” in red (Duolink™ In Situ Detection Reagent Red, λ Ex : 594, λ Em : 624).…”
Section: Commentarymentioning
confidence: 99%
“…In Figure 3, the ability of PLA to reveal post‐translational modifications of epidermal growth factor receptor (EGFR) are presented. An antibody recognizing EGFR is used in combination with an antibody recognizing ubiquitin or Nedd8, a ubiquitin‐like protein (Najor et al., 2017). In this experiment, the authors questioned whether Nedd8 and ubiquitin could compete for lysine residues on EGFR.…”
Section: Commentarymentioning
confidence: 99%